(untitled) (The Research of Medical Science Review, 2024)
Maintaining oral hygiene is essential for preventing periodontal disease, dental caries, and other oral health issues. Various tooth brushing techniques, such as the Bass, Fones, and Modified Stillman methods, have been promoted for their efficacy in plaque removal and gum health. However, the comparative effectiveness of these techniques remains inconclusive. This study aims to evaluate and compare the effectiveness of different toothbrushing methods on plaque removal and gingival health. To compare the effectiveness of different toothbrushing techniques (Bass, Fones, Modified Stillman, and Horizontal Scrub) in plaque removal and maintenance of gum health among adults.This cross-sectional study was conducted on a sample of 250 adults aged 18-60 years who were recruited from dental clinics. Participants were grouped based on the toothbrushing technique they reported using: Bass (n=70), Fones (n=60), Modified Stillman (n=60), and Horizontal Scrub (n=60). Plaque index and gingival index scores were recorded for each participant at baseline. A standardized education session was given to ensure proper technique use, followed by reassessment after two weeks. Data were analyzed using ANOVA and post-hoc tests to compare differences in plaque index and gingival index scores across the groups.Statistical analysis revealed significant differences in plaque index reduction and gingival health improvement across the groups (p<0.05). The Bass method group showed the greatest reduction in plaque index scores (mean reduction: 28%) and the highest improvement in gingival index scores (mean improvement: 22%). The Modified Stillman group showed similar results, with a mean plaque reduction of 24% and gingival improvement of 19%. The Fones method was less effective, with plaque reduction of 18% and gingival improvement of 15%. The Horizontal Scrub method had the lowest efficacy, with a mean plaque reduction of 12% and gingival improvement of 9%.The findings indicate that the Bass and Modified Stillman techniques are more effective in reducing plaque and enhancing gum health compared to the Fones and Horizontal Scrub methods. These results support recommending the Bass and Modified Stillman techniques in patient oral hygiene education for improved periodontal outcomes. Future research could further explore patient adherence to these methods over extended periods and their long-term impact on oral health.